FAKTOR- FAKTOR YANG MEMPENGARUHI MINAT MENABUNG NASABAH TABUNGAN SIMPANAN PELAJAR (SIMPEL) PADA PD. BPR SARIMADU KANTOR PUSAT BANGKINANG - Yulizar Yulizar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to determine the effect of Bank Services, Gifts and Savings Culture to the interest of saving depositors Savings Account Students (simple) in PD. BPR Sarimadu Headquarters Bangkinang. The sample in this research is partial nasaba using savings product of student saving which amounted to 98 respondents from 6134 PD customer saving customer population. BPR Sarimadu Headquarters Bangkinang. The sampling technique uses the proportionate stratified random sampling method. The data analysis used is multiple linear regression test. From result of this research indicate that variable of Bank Service, Gifts, and Culture Barhemat have significant influence simultaneously to interest of saving Student Savings Savings Account of PD. BPR Sarimadu Headquarters Bangkinang. The partial test result from the variable of Bank Service (X1) and Culture Frugal Variable (X3) has significant effect, while the Reward Variable (X2) has no significant effect to the interest of saving customers' savings deposits in PD. BPR Sarimadu Headquarters Bangkinang. Saving Variation of interest variables of 61.20% determined the Culture of Conserving, Service Bank, and Gifts, while the remaining 38.8% again determined by other variables outside the research model.